Accuracy of Linear Measurements Using Cone Beam Computed Tomography in Comparison with Clinical Measurements - Amir Reza Rokn; Kazem Hashemi; Solmaz Akbari; Mohammad Javad Kharazifard; Hamidreza Barikani; Mehrdad Panjnoosh (Tehran University of Medical Sciences, 2016)
Objectives: This study sought to evaluate the accuracy and errors of linear measurements of mesiodistal dimensions of Kennedy Class III edentulous space using cone beam computed tomography (CBCT) in comparison with clinical measurements. Materials and Methods: Nineteen Kennedy Class III dental arches were evaluated. An impression was made of each dental arch and poured with dental stone. The distance was measured on dental cast using a digital Vernier caliper with an accuracy of 0.1mm and on CBCT scans. Finally, the linear mesiodistal measurements were compared and the accuracy of CBCT technique was evaluated by calculating absolute value of errors, intra-class correlation coefficient and simple linear regression model. Results: In comparison with the cast method, estimation of size on CBCT scans had an error of -8.46% (underestimation) to 5.21% (overestimation). In 26.5% of the cases, an accepted error of ±1% was found. The absolute value of errors was found to be in the range of 0.21-8.46mm with an average value of 2.86 ±2.30mm. Conclusions: Although the measurements revealed statistically significant differences, this does not indicate a lower accuracy for the CBCT technique. In fact, CBCT can provide some information as a paraclinical tool and the clinician can combine these data with clinical data and achieve greater accuracy. Undoubtedly, calibration of data collected by clinical and paraclinical techniques and the clinician's expertise in use of CBCT software programs can increase the accuracy of implant placement.